2023
DOI: 10.3390/metabo13020257
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cyclodextrin-Assisted Extraction of Phenolics from Helichrysum italicum for Preparation of Extracts with Anti-Elastase and Anti-Collagenase Properties

Abstract: Helichrysum italicum is a plant traditionally used for skin-related disorders that is becoming an increasingly popular ingredient in cosmetic products. In this work, a “green” ultrasound-assisted extraction method for H. italicum phenolics was developed using skin-friendly cyclodextrins (CDs). Extraction conditions needed for the greatest yield of target compounds (total phenolics, phenolic acids, and flavonoids) were calculated. The composition of the extracts was determined using LC-MS and spectrophotometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 75 publications
1
19
0
1
Order By: Relevance
“…The TP, TPA, and TF content of the extracts are presented in Figure 1 . While TPA in OPT 1, as well as TP and TF in OPT 2, have been previously published in [ 10 ] ( Table S1 ), this research provides new information on TP and TF in OPT 1, as well as TPA in OPT 2. In our previous work, we optimized an HP-β-CD-assisted procedure for preparation of an extract containing a high amount of phenolic compounds.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…The TP, TPA, and TF content of the extracts are presented in Figure 1 . While TPA in OPT 1, as well as TP and TF in OPT 2, have been previously published in [ 10 ] ( Table S1 ), this research provides new information on TP and TF in OPT 1, as well as TPA in OPT 2. In our previous work, we optimized an HP-β-CD-assisted procedure for preparation of an extract containing a high amount of phenolic compounds.…”
Section: Resultsmentioning
confidence: 70%
“…In our previous work, we optimized an HP-β-CD-assisted procedure for preparation of an extract containing a high amount of phenolic compounds. The exhaustive extraction optimization, reported in the previous study [ 10 ], showed that a small amount (1.95%, w / w ) of lactic acid positively contributed to TPA extraction, while its presence exerted a negative influence on TP and TF extraction. As a result, two extracts were prepared using an optimized HP-β-CD-assisted procedure: OPT-1, with high TPA and prepared using lactic acid, while for the preparation of OPT-2, the extract high in TP and TF, lactic acid was not added.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations